MODERNISASI PERADILAN MELALUI E-LITIGASI DALAM PERSPEKTIF UTILITARIANISME JEREMY BENTHAM - Miftakur Rohman (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: e-litigation exists as a form of judicial modernization in Indonesia, to answer the challenges of a digitalized era. The Supreme Court (MA) as the holder of judicial power in accordance with its mission of increasing the credibility and transparency of the judiciary, as evidenced by the emergence of public service innovations in the form of E-litigation which was passed on August 19, 2019. E-litigation at trial can be done by teleconferance, which means that Technically, the parties can participate in several stages of the trial program wherever they are as long as it is according to the schedule and integrated with the internet network. All of this certainly provides convenience, both for trial administrators and justice seekers.